Isoflavones from Camphorosma lessingii Inhibit the Organic Anion Transporters OAT1 and OAT3 - Wang, Xinhui; Wang, Dujuan; Wang, Xue; Khutsishvili, Manana; Tamanyan, Kamilla; Fayvush, George; Atha, Daniel; Zhang, Youcai; Borris, Robert P. (Planta Medica, 2019)
Phytochemical investigation of Camphorosma lessingii has resulted in the isolation of four previously unreported isoflavones (1–4) and eight known compounds (5–12). Nine of these compounds (1–6, 8–10) are reported for the first time from members of the family Amaranthaceae. The structures of all isolated compounds were determined by spectroscopic methods, primarily one-dimensional and two-dimensional nuclear magnetic resonance and mass spectrometry. The absolute configuration of 6 was confirmed by circular dichroism. Inhibition of the organic anion transporters, OAT1 and OAT3, by the isolated compounds was evaluated. Among them, 7, 2′-dihydroxy- 6,8-dimethoxyisoflavone (1), 2′-hydroxy-6,7,8-trimethoxyisoflavone (2), 6,2′-dihydroxy-7,8-dimethoxyisoflavone (3), and 7-methoxyflavone (5) showed a significant inhibitory effect on 6-carboxyfluorescein uptake mediated by OAT1 and OAT3.
Keywords: Amaranthaceae; Camphorosma lessingii; isoflavone; organic anion transporters; OAT1; OAT3